Proceedings of the 2nd International Conference on Intelligent Technologies and Engineering Systems (ICITES2013) - Juang, Jengnan; Chen, Cheng-Yi; Yang, Cheng-Fu (Lecture Notes in Electrical Engineering, 2014)
This book includes the original, peer reviewed research papers from the 2nd International Conference on Intelligent Technologies and Engineering Systems (ICITES2013), which took place on December 12-14, 2013 at Cheng Shiu University in Kaohsiung, Taiwan. Topics covered include: laser technology, wireless and mobile networking, lean and agile manufacturing, speech processing, microwave dielectrics, intelligent circuits and systems, 3D graphics, communications, and structure dynamics and control.